2014
DOI: 10.1007/s00345-014-1435-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on success and complication rates after ureteroscopy

Abstract: No significant differences between female and male patients harboring ureteral stones with respect to intraoperative complications were detected. Although stone characteristics were comparable between groups, a small number of women had significantly more severe UTI's postoperatively. Our current therapy regimen for URS seems to be efficient and safe both for females and males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 15 publications
5
16
0
Order By: Relevance
“…This is consistent with other studies showing that patients with residual fragments had more urinary tract infections than patients without residual fragments. 2 With this study in mind, clearing the patient of all visible stones appears the most important variable in preventing an adverse outcome.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is consistent with other studies showing that patients with residual fragments had more urinary tract infections than patients without residual fragments. 2 With this study in mind, clearing the patient of all visible stones appears the most important variable in preventing an adverse outcome.…”
Section: Discussionmentioning
confidence: 90%
“…Ureteroscopy (URS) is increasingly selected as first-line therapy for renal and ureteral calculi, and it has proved to have higher success rates than extracorporeal shock wave lithotripsy. 2 Despite the widespread use of URS, past research reports a wide range of post-operative complications from 3.5% to up to 30%. 3,4 These complications can result in emergency department (ED) visits, hospital admissions, or returns to the operating room (OR).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 2070 articles were initially identified, and 14 full-text English language articles were included in the final review which fit our inclusion criteria (Fig. 1) [13,15,[18][19][20][21][22][23][24][25][26][27][28]. The total number of ureteroscopies included in these papers was 24,373, and the mean age was 51.2 years (range 42-61 years), male:female ratio of 3:2 and a mean BMI of 26.9 (range 23.7-31.8) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, there are many small, medium and highvolume prospective studies that have reported on the infectious complications following URS for renal stone disease [18][19][20][21][22][23][24][25][26][27][28][29]. Some studies have also looked at the risk factors for urinary infections following ureteroscopy and advised on strategies to reduce these risks.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies that have been published, factors that are directly related and lead to infectious complications and sepsis are not clearly defined (7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%